Technologies for the nitrogen oxides reduction from flue gas: A review - Gholami, Fatemeh; Tomas, Martin; Gholami, Zahra; Vakili, Mohammadtaghi (The Science of the total environment, 2020)
The required energy of the global industry is mostly generated from fossil fuel sources, such as natural gas, gasoline, diesel, oil, and coal. Nitrogen oxides are one of the main air pollutants that are produced from the combustion of fossil fuels in stationary and mobile sources. Development of new technologies to decrease the NOx emission from exhaust gases is essential due to the harmful effect of NOx on the environment and human health. Compared with pre-combustion and combustion methods (with <50% NOx removal efficiency), the post-combustion methods with higher efficiency (above 80%) have attracted more attention in NOx elimination. This review describes the currently used technologies of NOx abatement. Different available post-combustion methods of NOx removal, including selective catalytic reduction (using different types of reducing reagents, including ammonia, hydrogen, hydrocarbons, and carbon monoxide), selective noncatalytic reduction, wet scrubbing, adsorption, electron beam, nonthermal plasma, and electrochemical reduction of NOx, are discussed.
Keywords: Nitrogen oxides; Air pollution; Post-combustion; NO(x) removal